Энергонасыщенность -- важный геомеханический параметр геологической среды в горнотехнических системах - Козырев А.А.; Панин В.И.; Журавлева О.Г. (Федеральное государственное бюджетное учреждение науки Кольский научный центр Российской академии наук, 2018)
The relationship between the energy saturation of the geological environment and seismicity in the Khibiny mining-engineering system is indicated. The mechanisms of occurrence of mininginduced earthquakes are presented. A change in the seismic regime during the development of the Khibiny apatite-nepheline deposits is described. The causes and conditions are established which increase geodynamic risks in mining operations in the geological environment with low natural seismicity.
Keywords: ENERGY SATURATION OF GEOLOGICAL ENVIRONMENT; MINING-ENGINEERING SYSTEM; MINING-INDUCED SEISMICITY; GEODYNAMIC RISK; ЭНЕРГОНАСЫЩЕННОСТЬ ГЕОЛОГИЧЕСКОЙ СРЕДЫ; ГОРНОТЕХНИЧЕСКАЯ СИСТЕМА; ТЕХНОГЕННАЯ СЕЙСМИЧНОСТЬ; ГЕОДИНАМИЧЕСКИЙ РИСК; 622.83:550.36 (470.21)